Keyana Loves School - Tarpley, Natasha Anastasia, 1971-; Barlow, Charnelle Pinkney (New York : Little, Brown and Company, 2024)
"Second grader Keyana and her classmates celebrate their schools one hundredth anniversary by making quilt squares showcasing what they love most about their school"--
Ages 4-8.
Keywords: African American girls -- Juvenile fiction; Schools -- Juvenile fiction; Elementary schools -- Juvenile fiction; Classrooms -- Juvenile fiction; Patchwork quilts -- Juvenile fiction; Quilts -- Juvenile fiction; Quilting -- Juvenile fiction; African Americans -- Juvenile fiction; African American girls -- Fiction; Schools -- Fiction; Classrooms -- Fiction; Quilts -- Fiction; Quilting -- Fiction; African Americans -- Fiction; Picture books; School fiction